Effect of Probiotic Supplementation In Artificial Diets on Feed Digestibility And Growth of Tilapia (Oreochromis niloticus) - Kamil, Nurhidayatina; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on April 4 to June 1 2015 at Fish Nutrition Laboratory and Aquaculture Technology Laboratory, Fisheries and Marine Sciences Faculty, Riau University. This research aimed to determine the effect of probiotic supplementation in artificial diets on feed digestibility, feed efficiency, protein retention and growth of Tilapia (Oreochromis niloticus). Completely Randomized Design (CRD), was used with five treatments and three replications. The treatments were probiotic supplementation in diets with different concentration i.e : P0 (without probiotic supplementation in diets), P1 (probiotic sapplementation of 5 mL/kg diets), P2 (probiotic sapplementation of 10 mL/kg diets), P3 (probiotic sapplementation of 15 mL/kg diets) dan P4 (probiotic sapplementation of 20 mL/kg diets). Probiotic given through artificial diets with 30% of crude protein content. The results showed P4 (probiotic sapplementation of 20 mL/kg diets) were the best treatment with feed digestibility of 50,74%, feed efficiency of 29,27%, protein retention of 45,63%, and specific growth rate of 3,64% for Tilapia (Oreochromis niloticus).Key word : Diets, Digestibility, Growth, Oreochromis niloticus, Probiotic